2017
DOI: 10.3390/ijms18061211
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structurally Related Flavones Augment Cell Death Induced by rhsTRAIL

Abstract: TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) was identified as a powerful activator of apoptosis in tumor cells and one of the most promising candidates for cancer therapy with no toxicity against normal tissues. However, many tumor cells are resistant to TRAIL-induced apoptosis. The aim of this work was to analyze the improvement of the anticancer effect of rhsTRAIL (recombinant human soluble TRAIL) by nine flavones: 5-Hydroxyflavone, 6-Hydroxyflavone, 7-Hydroxyflavone and their new synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, certain types of cancer, including gliomas, are resistant to TRAIL-induced cell death ( 26 ). Chrysin has been shown to overcome TRAIL resistance in breast, pancreatic, cervical, colon, prostate and bladder cancer, as well as in hepatoma and melanoma cells ( 27 ). Thus, chrysin represents a potential therapeutic target for the development of clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain types of cancer, including gliomas, are resistant to TRAIL-induced cell death ( 26 ). Chrysin has been shown to overcome TRAIL resistance in breast, pancreatic, cervical, colon, prostate and bladder cancer, as well as in hepatoma and melanoma cells ( 27 ). Thus, chrysin represents a potential therapeutic target for the development of clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to apigenin, luteolin, and chrysin, other flavones have been reported to exert TRAIL-sensitizing effects in different types of cancer [54].…”
Section: Other Flavonesmentioning
confidence: 99%
“…Their results showed that chrysin, not the 5-FU combination, induces reactive oxygen species (ROS) generation, and consequently, inhibits the phosphorylation of protein kinase B (Akt) and mammalian target of rapamycin (mTOR; Lin et al, 2018). Nine novel structurally related flavones, 5-hydroxyflavone, 6-hydroxyflavone, 7-hydroxyflavone and their new synthetic derivatives 5-acetoxyflavone, 5-butyryloxyflavone, 6-butyryloxyflavone, 6-acetoxyflavone, 7-butyryloxyflavone, and 7-acetoxyflavone significantly augment tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis in SW480 and SW620 colon cancer cells (Bronikowska et al, 2017).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Their results showed that chrysin, not the 5‐FU combination, induces reactive oxygen species (ROS) generation, and consequently, inhibits the phosphorylation of protein kinase B (Akt) and mammalian target of rapamycin (mTOR; Lin et al, ). Nine novel structurally related flavones, 5‐hydroxyflavone, 6‐hydroxyflavone, 7‐hydroxyflavone and their new synthetic derivatives 5‐acetoxyflavone, 5‐butyryloxyflavone, 6‐butyryloxyflavone, 6‐acetoxyflavone, 7‐butyryloxyflavone, and 7‐acetoxyflavone significantly augment tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL)‐induced apoptosis in SW480 and SW620 colon cancer cells (Bronikowska et al, ). Another flavone baicalein, 5,6,7‐trihydroxyflavone, has been shown to inhibit the ERK signaling pathways, downregulate Ezrin and upregulate P53 pathway‐related proteins, DEPP and Gadd45a to suppress human colorectal cell invasion and proliferation and an induction of a marked apoptotic response (Chai, Xu, & Yan, ; Z. Chen, Hou, Gao, Song, & Feng, ; Su et al, ).…”
Section: Flavonoid Categories With Preventive and Therapeutic Effect ...mentioning
confidence: 99%